Using Nursery Rhymes in Teaching English for Young Learners at Childhood Education - Tira Nur Fitria (CV. Media Digital Publikasi Indonesia, 2023)
This study is a literature review that explores the use of nursery rhymes as a teaching tool for young learners in early childhood education. Nursery rhymes, also known as English children's songs, can be an enjoyable way to engage children and foster their interest in learning English. Additionally, singing nursery rhymes can support children's physical-motor, social, emotional, and intellectual development. When selecting nursery rhymes as teaching materials, teachers must consider the appropriateness of the content for the children's age and world, and the potential for the content to encourage discussion and exploration of values and problem-solving skills. The illustrations should also be evaluated for their alignment with the story and appropriateness for the children's age. From a linguistic standpoint, teachers must choose nursery rhymes that are suitable for the children's language level, that facilitate language learning, and that can serve as the basis for activities. While there are challenges associated with selecting and utilizing nursery rhymes as teaching materials, this study suggests that their use can be a valuable tool in the early childhood education classroom